Development of Interactive Learning Media Based on Lectora Inspire for Science Subjects to Improve Science Literacy of Fifth Grade Elementary School Students: Pendidikan Sekolah Dasar - Kurniawan, Nasya Eka; Kurnia, Ira Restu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
Interactive Learning Media for Science Subjects Water Cycle Material based on Lectora Inspire was developed based on problems that occurred in the teaching and learning process in class V Al Bari' SDIT AS Salam. This research was developed with a product in the form of a Desktop application that can be accessed using a computer in the school computer lab as a use of school infrastructure facilities. The purpose of this study was to develop interactive learning media for science subjects for class V based on Lectora Inspire at SDIT As Salam, and to determine the level of feasibility of interactive learning media for science subjects Cycle material based on Lectora Inspire based on the results of assessments by material experts, media experts, language experts, and students of class V Al Bari' SDIT As Salam. The method used in this study is the Research and Development (R&D) method with the ADDIE development model which is limited to three stages, namely, Analysis, Design, and Development. The final product produced is a Desktop application that has been validated by material experts, media experts, and language experts and has been tested on class V Al Bari' students. The results of the feasibility test of media experts were 96%, material experts 95%, and language experts 76%. The accumulation of assessments from experts obtained a score of 89%, getting a very feasible category. Assessment by students 91.1%, and teacher assessment 97%. The accumulation of assessments from students and teachers obtained a score of 94.5%, so it is included in the very practical category. So that learning media based on Lectora Inspire as a whole is very feasible for use by students in learning activities.